Evaluation of the Low-Level Laser Therapy in Pain, Bite Force, and Mouth Opening Following Midfacial Trauma - Mateus Diego Pavelski; Maicon Douglas Pavelski; Luana Ferreira Oliveira; Helio Doyle Pereira da Silva; Lucio Frigo; Osvaldo Magro-Filho (Life)
Low-level laser therapy (LLLT) is known for its biostimulant properties, which can reduce inflammation and promote tissue regeneration. The present study is randomized, blinded, and placebo-controlled and aims to investigate the role of LLLT in the postoperative recovery of facial fractures. Patients with fractures of the zygomatic bone are selected and divided into two groups: low-level laser and red placebo light. The patients are evaluated for bite force, pain, mouth opening, and paresthesia in the pre-operatory day, on days 1, 2, 7, and 14. The trismus data demonstrated better results in the laser with a significant difference in the periods 7 and 14 days, with p-values of 0.0442 and 0.026, respectively. Regarding the bite force analyzed, no statistically significant differences were observed. In the pain scale comparison, there was a difference between the PLACEBO group and the LASER group for day 1 (p = 0.011), day 2 (p = 0.001), 7 (p = 0.001), and 14 days (p = 0.010). In the evaluation of paresthesia, on days 7 and 14, there were better results in the LASER group with p = 0.012 and p = 0.001. The laser acted as a moderator of the healing process, having a considerable effect on the aspects of trismus, pain, postoperative paresthesia, and bite force.